Repeated long-term cover cropping and nitrogen fertilization enhance soil multifunctionality - Lin Li; Wanyu He; Qilong Du; Xue Zhao; Minghui Meng; Guangjin Wu; Guangxi Liu; Simeng Wang; Jun Wang; Fazhu Zhao; Jieying Wang (Agriculture, Ecosystems & Environment, 2026)

Mechanistic insights and mitigation strategies for brominated dioxin formation from thermal treatment of hexabromocyclododecane waste - Heng Zhang; Lyumeng Ye; Junkai Lin; Zhiyuan Xu; Rong Jin; Dongyao Chen; Xin Zhou; Bingcheng Lin; Minghui Zheng (Waste Management, 2026)

Chlorinated and brominated persistent organic pollutants in industrial thermal processes: Emission profiles and radical-mediated formation pathways - Junkai Lin; Bingcheng Lin; Zhiyuan Xu; Guohua Zhu; Rong Jin; Lyumeng Ye; Dongyao Chen; Xin Zhou; Minghui Zheng (Journal of Environmental Sciences, 2026)

The mixed cover crops and nitrogen fertilization decrease the soil microbial dormancy - Simeng Wang; Xue Zhao; Wanyu He; Jieying Wang; Minghui Meng; Xiya Xiong; Min Xie; Guangjin Wu; Qilong Du; Lin Li; Guangxi Liu; Jun Wang; et al. (Plant and Soil, 2026)

Physics-informed neural networks with learning-rate scheduling and domain decomposition for forward and inverse analysis of offshore flexible piles under complex loading - Fayun Liang; Minghui Tao; Lin Li; Hao Zhang (Ocean Engineering, 2026)

Mechanistic insights into the role of nitrogen configurations driving efficient activation of low-dose ferrate (VI) for sulfonamides elimination - Zhikang Deng; Jinyao Zhu; Xi Chen; Minghui Xiang; Hui Lin; Junwei Ma; Song Cui; Zulin Zhang (Journal of Environmental Chemical Engineering, 2026)

Fluorinated-MXene-enabled self-powered nanofiber membrane for synchronous fog harvesting and atmospheric pollution monitoring - Shuai Ma; Wei Yuan; Xueni Jiang; Jing He; Minghui Xiao; Hong Lin; Jiaqing Xiong; Yuyue Chen; Desuo Zhang (Journal of Cleaner Production, 2026)

Stimulus-responsive fluorine-doped silicon nanodots polymer films exhibiting dual-mode afterglow emission for intelligent information encryption - Lele Gao; Yulu Liu; Jiasheng Lin; Weigang Zheng; Huihui Wang; Lei Cao; Wen-Fei Dong; Minghui Zan; Shizhong Luo (Chemical Engineering Journal, 2026)

Deciphering the flavor chemistry of traditional and novel nattos: A multidisciplinary approach integrating amino acid profiling, volatile compound analysis, and molecular docking - Qile Zhang; Jiawei Wu; Yiu Ming Cheung; Yuhong Lin; Xinyi Deng; Minghui Li; Chufeng He; Dianjing Guo; Cheng Li; Hon Ming Lam; Wing Tak Wong (Food and Humanity, 2026)

Red phosphorus triggers endogenous iron activation of sludge biochar for peroxymonosulfate activation: Unravelling superoxide radical and non-radical degradation mechanisms - Minghui Xiang; Zhikang Deng; Yongfei Ma; Yifan Liu; Xiaoyu Xiang; Han Ding; Ranran Zhang; Hui Lin; Junwei Ma; Yongzhen Ding; Zulin Zhang (Journal of Environmental Chemical Engineering, 2026)

Spatiotemporal variations of chlorinated polycyclic aromatic hydrocarbons in Yellow Sea sediments: An eight-year field monitoring study - Xin Yang; Yunyong She; Qian Zhao; Dan Xu; Shenjie Li; Yueyao Yang; Guohua Zhu; Zhefu Yu; Junpeng Li; Bingcheng Lin; Minghui Zheng; Rong Jin (Journal of Hazardous Materials, 2026)

Polyploidy and zinc nanoparticles enhanced cadmium tolerance by regulating antioxidants and transport proteins - Jingwen Liu; Fozia Ghouri; Lixia Sun; Zihang Lin; Minghui Zhong; Muhammad Farooq; Muhammad Qasim Shahid (Plant Cell Reports, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Coping or not? A stackelberg game perspective on European Union strategies for the rising Chinese electric vehicle market share - Yu Lin; Minghui Liu; Tieqiao Tang; Na Yan; Dongxu Chen (Journal of Cleaner Production, 2026)

Elimination performance of NOx and chlorobenzene over VOx/TiO2-based commercial SCR catalysts at low temperature: Sulfur poisoning and regeneration - Yunfeng Ma; Jiayao Wu; Jianwen Lai; Hongbo Qi; Fanxiang Meng; Bingcheng Lin; Rong Jin; Zhongkang Han; Minghui Zheng; Xiaodong Li; Xiaoqing Lin (Chemical Engineering Journal, 2026)

Comparative analysis of Tibetan human milk fat globule membrane proteins across lactation stages - Shenglong Du; Xiaomei Zhang; Minghui Zhang; Tie Lin; Bin Liu; Mengna Jing; Junying Zhao; Lijun Chen (Food Research International, 2026)

Vertical structure of the aerosols in the troposphere over the North China Plain: An analysis based on observations and simulations from 2007 to 2022 - Jiajun Xiong; Yi Wang; Minghui Tao; Wenhui Dong; Lin Zhou; Lunche Wang (Atmospheric Research, 2026)

Upcycling plastic waste into high-value gases via pulsed joule heating for economic and carbon benefits - Zitong Wan; Xuan Xie; Yunfeng Ma; Guohua Zhu; Rong Jin; Bingcheng Lin; Minghui Zheng (Chemical Engineering Journal, 2025)

In-situ growth of TiO2 nanoparticles on MXene to construct 3D copper-based catalyst for methanol steam reforming - Rensheng Song; Guangbo Zhou; Minghui Lian; Haodong Chen; Lei Wang; Jinxiao Li; Chunhua Yang; Xinyu Lin; Liwei Pan (Fuel, 2025)

Enhanced low-temperature catalytic activity and SO2 resistance in ethane oxidation over Pt-CoZr catalysts: Insights into the promoting effects of Pt and Zr - Ling Wang; Beilong Lin; Zhiyuan Gong; Minghui Tang; Shengyong Lu; Jianhua Yan (Journal of Environmental Chemical Engineering, 2025)

Joule heating-driven efficient catalytic oxidation of chlorobenzene over MnCe-nickel foam: A flexible and energy-efficient strategy - Fanxiang Meng; Yunfeng Ma; Xiaojun Ma; Ling Wang; Feiyi Zhou; Bingcheng Lin; Rong Jin; Minghui Zheng; Chen Sun; Tong Chen (Chemical Engineering Journal, 2025)

An attractive vaccine candidate based on AP205 VLPs fusing with a receptor-binding domain of a newly emerged porcine deltacoronavirus strain in China - Xinyue Chang; Zhenyuan Zhang; Yilian Chen; Minghui Zhang; Fei Fei; Chenhao Ma; Zhiying Wang; Fazhi Xu; Lin Li; Xinxin Shan; Liang Li; Pei Sun; et al. (Veterinary Microbiology, 2025)

Charge/conformation-transformable phosphopeptide@hollow covalent organic frameworks as molecular gates for electrochemical analysis - Lin Wang; Minghui Wang; Gaoxiang Wang; Haojie Xie; Yu Hang; Dongmei Zhang; Sha Zhu; Xiafei Hu; Genxi Li (Chemical Engineering Journal, 2025)

The chemical basis of aroma/taste and color formation in green tea infusion during cold brewing revealed by metabolomics analysis - Chen Yang; Zhaojun Wang; Minghui Xu; Kaikai Wei; Qianying Dai; Xiaochun Wan; OiPo Leong; Runze Lin; Chuanjian Cui; Ruyan Hou (Food Chemistry, 2025)

A biomimetic liposome platform targeting non-small cell lung cancer to modulate the inflammatory and metabolic microenvironment for enhanced therapy - Xinyu Jiang; Pengfei Mao; Minghui Wang; Dingchao Shen; Linyi Zhang; Yingyi Zhao; Xindan Liang; Zihao Huang; Yunzhi Wang; Yinhao Lin; Zihao Tao; Yuqi Han; et al. (Chemical Engineering Journal, 2025)

Genetic Diversity in Three Sinipercine Fishes Based on Mitochondrial D-Loop and COX1 Sequences - Minghui Lin; Xu-Fang Liang; Ke Lu; Ming Zeng; Junjie Gao; Yaqi Dou; Yulan Kuang; Qiwei Zhang (Fishes, 2025)
Mandarin fish (Siniperca chuatsi), golden mandarin fish (Siniperca scherzeri), and Coreoperca whiteheadi are three important aquaculture species in China facing several threats to their production. Genetic diversity was assessed by sequencing the mitochondrial D-loop and cox1 regions in 207 individuals across nine populations. The genetic diversity analysis, based on the concatenated sequences, revealed that the total haplotype diversity was high across all sinipercine fish populations. Population differentiation analysis revealed that most genetic variation was within populations: 74.5% in S. chuatsi (p

Comprehensive transcriptome and metabolome analysis of the adaptability and detoxification ability of Spodoptera frugiperda larvae to tobacco - Minghui Xie; Yongzhi Zhong; Lulu Lin; Guangling Zhang; Ning Wei; Feng Zhang; Haoliang Chen (Journal of Insect Physiology, 2025)

Dynamic whole genome amplification using digital microfluidics for single-cell sequencing - Qingyu Ruan; Changrui Shi; Xiaoye Lin; Weidong Ruan; Minghui Xu; Chaoyong Yang; Yukun Ren (Chemical Engineering Journal, 2025)

UCHL1-Mediated Spastin Degradation Regulates Microtubule Severing and Hippocampal Neurite Outgrowth - Ao Ma; Zhi Liang; Hongde Zhang; Zhichao Meng; Jiehao Zhu; Shu Chen; Qisheng Lin; Tao Jiang; Minghui Tan (Journal of Molecular Neuroscience, 2025)

Are there links between nutrient inputs and the response of microbial carbon use efficiency or soil organic carbon? A meta-analysis - Minghui Liu; Hanyang Lin; Junmin Li (Soil Biology and Biochemistry, 2025)

An efficient fungi-biochar-based system for advancing sustainable management of combined pollution - Ying Xia; Minghui Deng; Tao Zhang; Junjun Yu; Xinda Lin (Environmental Pollution, 2025)

Research on the explosive characteristics and suppression mechanisms of gas generation during thermal runaway of batteries in a charged state - Jianqi Zhang; Fangzhou Li; Lin Yu; Yuhui Wang; Kuo Wang; Chongye Chang; Minghui Li; Wenhao Hao; Xinming Qian (Chemical Engineering Journal, 2025)

Variation profiles, formation mechanisms, and emission risks of brominated flame retardant compounds during cement kiln co-processing of hexabromocyclododecane-containing waste - Xin Li; Yahui Liu; Bingcheng Lin; Guohua Zhu; Jian Wang; Xiao Wang; Yueyao Yang; Shanshan Zhang; Guorui Liu; Rong Jin; Minghui Zheng (Journal of Hazardous Materials, 2024)

Insights into a photo-driven laccase coupling system for enhanced photocatalytic oxidation and biodegradation - Ying Xia; Minghui Deng; Tao Zhang; Nannan Yuan; Xinda Lin (Chemical Engineering Journal, 2024)

Lactobacillaceae-mediated eye-brain-gut axis regulates high myopia-related anxiety: from the perspective of predictive, preventive, and personalized medicine - Yuze Mi; Ke Chen; Shaokai Lin; Luyao Tong; Jiawei Zhou; Minghui Wan (EPMA Journal, 2024)

Genetic insights into hypoxia tolerance in silver sillago (Sillago sihama) through QTL mapping and SNP association analysis - Minghui Ye; Lingwei Kong; Zhenghao Jian; Zhongqi Qiu; Xinghua Lin; Yulei Zhang; Yang Huang; Guangli Li; Changxu Tian (Aquaculture, 2024)

Emission, distribution and formation characteristics of polybrominated dibenzo-p-dioxins and dibenzofurans during co-disposal of hexabromocyclododecane-containing waste in cement kiln - Jian Wang; Bingcheng Lin; Xiao Wang; Guorui Liu; Rong Jin; Jukun Xiong; Jianping Guo; Yinming Li; Minghui Zheng (Science of The Total Environment, 2024)

Bimetallic loaded ZIF-8 with peroxidase-like and photothermal activities for sensitive detection and efficient elimination of Listeria monocytogenes - Tingting Su; Yuting Chang; Minghui Lu; Xianfeng Lin; Zhiyuan Ning; Shijia Wu; Zhouping Wang; Nuo Duan (Chemical Engineering Journal, 2024)

In-situ surface reconstruction of CsPbl3 perovskite for efficient and stable solar cells - Weideren Dai; Yanzhuo Gou; Huili Wei; Chang Chen; Zexun Pan; Xu zhang; Liangyou Lin; Minghui Shang; Qunchao zhang; Xianbao Wang; Qidong Tai; Jinhua Li (Chemical Engineering Journal, 2024)

Insight into the inhibition mechanisms of Ca-, N-, S-containing compounds on persistent organic pollutant formation from the thermal reaction of anthracene on copper chloride - Xiao Wang; Bingcheng Lin; Jian Wang; Yunfeng Ma; Rong Jin; Guorui Liu; Minghui Zheng (Chemical Engineering Journal, 2024)

RpedOBP1 plays key roles in aggregation pheromones reception of the Riptortus pedestris - Yongzhi Zhong; Rui Tang; Lulu Lin; Wei Zhao; Shuang Wei; Feng Zhang; Md Kafil Uddin; Minghui Xie; Haoliang Chen (Pesticide Biochemistry and Physiology, 2024)

Atractylenolide I ameliorates sepsis-induced cardiomyocyte injury by inhibiting macrophage polarization through the modulation of the PARP1/NLRP3 signaling pathway - Dan Wang; Zhiqiang Lin; Yiqing Zhou; Meixia Su; Haiwang Zhang; Lixia Yu; Minghui Li (Tissue and Cell, 2024)

Characteristics and degradation mechanisms of polychlorinated naphthalenes in surface soil in Yangtze River Delta, China - Zherui Zhang; Guohua Zhu; Yahui Liu; Xin Zhou; Bingcheng Lin; Ziyuan Qi; Shanshan Zhang; Yueyao Yang; Xin Li; Rong Jin; Minghui Zheng (Chemosphere, 2024)

Reduction of haemoglobin is related to metal mixtures exposure in Chinese preschoolers: Joint effect models - Ye Fu; Minghui He; Yang Liu; Mingzhu Li; Meiqin Zhu; Yan Wang; Wei Lin; Lili Yu; Liting Yang; Yao Zhang; Yanli Liu; Hongxian Ji; et al. (Journal of Trace Elements in Medicine and Biology, 2024)

Demographic analysis of the biological parameters of Spodoptera frugiperda after sublethal exposure to insecticides - Lulu Lin; Minghui Xie; Yongzhi Zhong; Guangling Zhang; Feng Zhang; Haoliang Chen (Crop Protection, 2024)

Identification of Key Factors in Cartilage Tissue During the Progression of Osteoarthritis Using a Non-targeted Metabolomics Strategy - Shiyu Sun; Minghui Chen; Tingting Zhang; Yanyan Wang; Weijun Shen; Tao Zhang; Jian Liu; Haidan Lan; Jianyuan Zhao; Fuqing Lin; Xuan Zhao (Phenomics, 2024)
This research was to reveal the key factors in the progression of osteoarthritis (OA) using non-targeted metabolomics and to find targeted therapies for patients with OA. Twenty-two patients with knee OA scheduled for total knee arthroplasty were divided into two groups: Kellgren–Lawrence (KL) grade 3 ( n = 16) and grade 4 ( n = 6), according to plain X-rays of the knee. After the operation, the cartilages of femur samples were analyzed using non-targeted metabolomics. When compared with grade 3 patients, the levels of choline, 2-propylpiperidine, rhamnose, and monomethyl glutaric acid were higher; while 1-methylhistamine, sphingomyelin (SM) (d18:1/14:0), zeranol, 3- (4-hydroxyphenyl)-1-propanol, 5-aminopentanamide, dihydrouracil, 2-hydroxypyridine, and 3-amino-2-piperidone were lower in grade 4 patients. Furthermore, some metabolic pathways were found to be significantly different in two groups such as the pantothenate and coenzyme A (CoA) biosynthesis pathway, the glycerophospholipid metabolism pathway, histidine metabolism pathway, lysine degradation pathway, glycine, serine and threonine metabolism pathway, fructose and mannose metabolism pathway, the pyrimidine metabolism pathway, and beta-alanine metabolism pathway. This work used non-targeted metabolomics and screened out differential metabolites and metabolic pathways, providing a reliable theoretical basis for further study of specific markers and their specific pathways in the progression of OA.

Effects of different oxidants on the behaviour of microplastic hetero-aggregates - Minghui Li; Zheng Li; Feiyong Chen; Bingfang Shi; Yonggang Li; Zhaoliang Zhu; Lin Wang; Yan Jin (Journal of Hazardous Materials, 2024)

Unstable geomorphologic fabric impacted by excess magmas and propagating rifts in the central West Philippine Basin - Weidong Luo; Pin Yan; Gaowen He; Yufang Tan; Ruiying Ye; Hongjun Chen; Zhen Lin; Houjin Wang; Minghui Zuo; Changliang Chen; Junhui Yu; Yanlin Wang (Geomorphology, 2024)

Screening of Streptomyces strains helping arbuscular mycorrhizal symbiosis against pepper (Capsicum annuum L.) Phytophthora blight - Xin WANG; Yifan LIU; Baiping HE; Minghui LI; Xiangui LIN; Fuyong WU; Junli HU (Pedosphere, 2024)

Enhanced peroxymonosulfate activation via MOF-derived bimetal core-shell Co-Fe@NC hybrids to degrade emerging pollutants - Hui Li; Xinlei Ren; Wenxue Pan; Shiting Zhu; Jin Zhang; Zhiyuan Yang; Liu Qian; Yueying Wang; Yujing Huang; Lin Guo; Minghui Xiang (Journal of Environmental Chemical Engineering, 2024)

A microelectrode electrochemical sensing platform based on heteroatoms doped carbon nanotubes arrays with peroxidase-like activity for in-situ detection in live cell - Yan Zhang; Tao Lin; Minghui Han; Min Hu; Yun Xu; Wei Huang; Fei Xiao; Anshun Zhao (Analytica Chimica Acta, 2024)

Dosage and exposure time effects of two micro(nono)plastics on arbuscular mycorrhizal fungal diversity in two farmland soils planted with pepper (Capsicum annuum L.) - Baiping He; Zihao Liu; Xin Wang; Minghui Li; Xiangui Lin; Qingqing Xiao; Junli Hu (Science of The Total Environment, 2024)

Nickel-doped microtubular CeVO4 inspired by wood powder structure for visible light photocatalytic degradation of methylene blue and bacterial inactivation - Chang Ma; Bin Yin; Ying Zhang; Junfeng Chen; Shuo Zhang; Zuopeng Lin; Xing Gao; Minghui Guo (Journal of Water Process Engineering, 2024)

Norepinephrine-induced hydrophilic Pd aerogels with photothermal-boosted multienzyme-like activity for chemodynamic therapy of MRSA infections - Minghui Wang; Na Li; Nanyun Lin; Yingying Wu; Wei Zhou; Ximei Sun; Peixian Wu; Qian Fu; Wenjie Wang; Zheng Liu; Shuiyuan He; Mengyu Zhou; et al. (Chemical Engineering Journal, 2024)

Net effect of air pollution controls on health risk in the Beijing–Tianjin–Hebei region during the 2022 winter Olympics and Paralympics - Changqing Lin; Peter K.K. Louie; Alexis K.H. Lau; Jimmy C.H. Fung; Zibing Yuan; Minghui Tao; Xuguo Zhang; Md. Shakhaoat Hossain; Chengcai Li; Xiang Qian Lao (Journal of Environmental Sciences, 2024)

Isolation and characterization of 48 SNP markers of sleepy cod, Oxyeleotris lineolata by whole-genome resequencing - Jiajia Fan; Dongmei Ma; Huaping Zhu; Minghui Lin; Huanhuan Su; Zaixuan Zhong (Conservation Genetics Resources, 2023)

Non-target and target analysis to identify and characterize thiophenes in soil from an abandoned coking plant - Qiaofeng Ai; Lirong Gao; Di Huang; Jing Yang; Qiang Fu; Xuan Zheng; Yang Liu; Lin Qiao; Jiyuan Weng; Minghui Zheng (Journal of Hazardous Materials, 2023)

Prussian blue analogues derived magnetic FeCo@GC material as high-performance metallic peroxymonosulfate activators to degrade tetrabromobisphenol A over a wide pH range - Liu Qian; Hui Li; Dengsong Zhang; Lin Guo; Wenxue Pan; Jin Zhang; Minghui Xiang (Environmental Science and Pollution Research, 2023)

The paleo-lithospheric structure and rifting-magmatic processes of the northern South China Sea passive margin - Zhongxian Zhao; Zhen Sun; Ning Qiu; Minghui Zhao; Jiazheng Zhang; Fucheng Li; Jian Lin; Eun Young Lee (Gondwana Research, 2023)

Implications for biological invasion of non‐native plants for sale in the world's largest online market - Achyut Kumar Banerjee; Tien Ming Lee; Hui Feng; Xinru Liang; Yuting Lin; Jiakai Wang; Minghui Yin; Hao Peng; Yelin Huang (Conservation Biology, 2023)
Internet trade is increasingly recognized as a dispersal pathway of non‐native plant species that is difficult to monitor. We sought to identify non‐native flora present in the Chinese online market, the largest e‐commerce market globally, and to decipher the effect of existing trade regulations, among other variables, on e‐trading patterns and to inform policy. We used a comprehensive list of 811 non‐native plant species in China present in 1 of the 3 phases of the invasion continuum (i.e., introduced, naturalized, and invasive). The price, propagule types, and quantities of the species offered for sale were retrieved from 9 online stores, including 2 of the largest platforms. Over 30% of the non‐native species were offered for sale in the online marketplaces; invasive non‐native species dominated the list (45.53%). No significant price difference was observed across the non‐native species of the 3 invasion categories. Among the 5 propagule types, a significantly higher number of non‐native species were offered for sale as seeds. The regression models and path analyses consistently revealed a direct positive effect of the number of uses and species’ minimum residence time and an indirect effect of biogeography on the pattern of trade in non‐native plant species when minimal phylogenetic signal was detected. A review of the existing phytosanitary regulations in China revealed their inadequacy in managing e‐trading of non‐native plant species. To address the problem, we propose integration of a standardized risk assessment framework that considers perceptions of stakeholders and is adaptable based on continuous surveillance of the trade network. If implemented successfully, the measures could provide a template for other countries to strengthen trading regulations for non‐native plant species and take proactive management measures.

An artificial interfacial layer with biomimetic ionic channels towards highly stable Li metal anodes - Yiju Li; Tianshuai Wang; Junjie Chen; Xudong Peng; Minghui Chen; Bin Liu; Yongbiao Mu; Lin Zeng; Tianshou Zhao (Science Bulletin, 2023)

Remarkably efficient Pt/CeO2–Al2O3 catalyst for catalytic hydrodeiodination of monoiodoacetic acid: Synergistic effect of Al2O3 and CeO2 - Minghui Li; Wen Li; Yaning Yang; Dailiang Yu; Jingling Lin; Rui Wan; Hongjie Zhu (Chemosphere, 2023)

Conservation and sustainable development of coastal species of horticultural importance: insights from genetic and environmental patterns at spatio-temporal scale - Achyut Kumar Banerjee; Jiakai Wang; Hui Feng; Yuting Lin; Xinru Liang; Minghui Yin; Hao Peng; Weixi Li; Tengjiao Li; Wuxia Guo; Yelin Huang (Biodiversity and Conservation, 2023)

Target and non-target analysis of organochlorine pesticides and their transformation products in an agrochemical-contaminated area - Di Huang; Lirong Gao; Shuai Zhu; Lin Qiao; Yang Liu; Qiaofeng Ai; Chi Xu; Wenwen Wang; Meiling Lu; Minghui Zheng (Chemosphere, 2023)

Integrating Ecosystem Health and Services for Assessing Ecological Risk and its Response to Typical Land-Use Patterns in the Eco-fragile Region, North China - Yisen Wang; Zhonghua Yang; Minghui Yu; Ruyu Lin; Lei Zhu; Fengpeng Bai (Environmental Management, 2023)

Secondary pollution of microplastic hetero-aggregates after chlorination: Released contaminants rarely re-adsorbed by the second-formed hetero-aggregates - Yan Jin; Minghui Li; Feiyong Chen; Lin Wang; Lijie Zhang; Zhigang Yang; Ning Wang; Jie Fu; Yang Yu; Xiaoxiang Cheng; Daoji Wu (Journal of Hazardous Materials, 2023)

Model Evaluation of Indoor Exposure to Polychlorinated Dibenzo-p-Dioxins and Dibenzofurans and Polycyclic Aromatic Hydrocarbons from Household Fuel Combustion in Rural Areas of Tibetan Plateau - Rong Jin; Minghui Zheng; Lili Yang; Gerhard Lammel; Xin Zhou; Yuxiang Sun; Changzhi Chen; Bingcheng Lin; Guorui Liu (Exposure and Health, 2023)

Trade-offs between fertilizer-N availability and Cd pollution potential under crop straw incorporation by 15 N stable isotopes in rice - Anqi Shan; Lukuan Huang; Dan Chen; Qiang Lin; Rongjie Liu; Mei Wang; Kyong Ju Kang; Minghui Pan; Gang Wang; Zhenli He; Xiaoe Yang (Environmental Science and Pollution Research, 2023)

Free radical mechanism of toxic organic compound formations from o-chlorophenol - Xiaoyun Liu; Guorui Liu; Shuting Liu; Linjun Qin; Bingcheng Lin; Mingxuan Wang; Lili Yang; Minghui Zheng (Journal of Hazardous Materials, 2023)

Intercropping with maize (Zea mays L.) enhanced the suppression of pepper (Capsicum annuum L.) Phytophthora blight by arbuscular mycorrhizal fungi - Junli Hu; Shaowei Hou; Peng Cai; Minghui Li; Zhang Cheng; Fuyong Wu; Xiangui Lin (Journal of Soils and Sediments, 2023)

Concentrations, congener patterns, and correlations of unintentional persistent organic pollutants in cement kilns co-processing hazardous waste - Changzhi Chen; Haoyang Wang; Guorui Liu; Bingcheng Lin; Lili Yang; Rong Jin; Yuxiang Sun; Jianping Guo; Yinming Li; Nan Yang; Aihong Li; Changliang Li; et al. (Science of The Total Environment, 2023)

Comparison of groundwater hydrogeochemistry of karst areas in northern and southern China with emphasis on their performance in karst development - Peng Yuming; Xiao Qiong; Xue Honglei; Lv Minghui; Lin Guangqi; Zhao Haijuan; Wu Peiyan; Guo Yongli (Carbonates and Evaporites, 2022)

The roles and performance of arbuscular mycorrhizal fungi in intercropping systems - Minghui Li; Junli Hu; Xiangui Lin (Soil Ecology Letters, 2022)

Climatology of aerosol types and their vertical distribution over East Asia based on CALIPSO lidar measurements - Lu Gui; Minghui Tao; Yi Wang; Lunche Wang; Liangfu Chen; Changqing Lin; Jinhua Tao; Jun Wang; Chao Yu (International Journal of Climatology, 2022)
Aerosol vertical distribution generally determines their health impacts and climate effects. By using long‐term (2007–2019) CALIPSO lidar measurements, we present a large‐scale insight into the climatology of aerosol types and their vertical structure over East Asia. Despite the low sampling frequency, comparison with MODIS aerosol optical depth (AOD) shows that the integrated CAIPSO vertical extinction can reasonably reproduce spatial patterns of the aerosol loading. With the unique advantage of active detection, CALIPSO reveals an obvious enhancement of the night‐time AOD due to worse diffusion conditions. Moreover, long‐range transport of different aerosols including dust, polluted dust, and smoke has substantial contribution to the aerosol loading over East Asia. Pure dust particles are mainly concentrated over the deserts with notable dust transport belts (dust AOD > 0.2 at 532 nm) along downwind regions during winter and spring. By contrast, polluted dust is prevalent over the downstream eastern China with much higher AODs throughout the year. In particular, AOD of polluted dust (~0.5) is higher in winter rather than in spring, which is consistent with their seasonal occurrences. Smoke aerosols usually appear in the night‐time over southern China. The top heights of aerosols are around 4–6 km, with dust and smoke having higher extinction at upstream regions. The climatology of these aerosol types and vertical distribution can provide a significant constraint for associated studies of air quality and climate effects.

Genetic and biological characteristics of the globally circulating H5N8 avian influenza viruses and the protective efficacy offered by the poultry vaccine currently used in China - Pengfei Cui; Xianying Zeng; Xuyong Li; Yanbing Li; Jianzhong Shi; Conghui Zhao; Zhiyuan Qu; Yanwen Wang; Jing Guo; Wenli Gu; Qi Ma; Yuancheng Zhang; et al. (Science China Life Sciences, 2022)
The H5N8 avian influenza viruses have been widely circulating in wild birds and are responsible for the loss of over 33 million domestic poultry in Europe, Russia, Middle East, and Asia since January 2020. To monitor the invasion and spread of the H5N8 virus in China, we performed active surveillance by analyzing 317 wild bird samples and swab samples collected from 41,172 poultry all over the country. We isolated 22 H5N8 viruses from wild birds and 14 H5N8 viruses from waterfowls. Genetic analysis indicated that the 36 viruses formed two different genotypes: one genotype viruses were widely detected from different wild birds and domestic waterfowls; the other genotype was isolated from a whopper swan. We further revealed the origin and spatiotemporal spread of these two distinct H5N8 virus genotypes in 2020 and 2021. Animal studies indicated that the H5N8 isolates are highly pathogenic to chickens, mildly pathogenic in ducks, but have distinct pathotypes in mice. Moreover, we found that vaccinated poultry in China could be completely protected against H5N8 virus challenge. Given that the H5N8 viruses are likely to continue to spread in wild birds, vaccination of poultry is highly recommended in high-risk countries to prevent H5N8 avian influenza.

Phylogeographic structure and population demography of the leopard mandarin fish (Siniperca scherzeri) in the Pearl River drainage - Minghui Lin; Xufang Liang; Junjie Gao; Yaqi Dou; Yulan Kuang; Qiwei Zhang (Environmental Biology of Fishes, 2022)

Arbuscular mycorrhizal fungus suppresses tomato (Solanum lycopersicum Mill.) Ralstonia wilt via establishing a soil–plant integrated defense system - Minghui Li; Shaowei Hou; Junhua Wang; Junli Hu; Xiangui Lin (Journal of Soils and Sediments, 2021)

Assessing tree height and density of a young forest using a consumer unmanned aerial vehicle (UAV) - Zhenbang Hao; Lili Lin; Christopher J. Post; Yusen Jiang; Minghui Li; Nibin Wei; Kunyong Yu; Jian Liu (New Forests, 2021)

Comparative Transcriptome Analysis of Heart Tissue in Response to Hypoxia in Silver Sillago (Sillago sihama) - Wanida Saetan; Minghui Ye; Xinghua Lin; Xiaozhan Lin; Yulei Zhang; Yang Huang; Tao Du; Guangli Li; Changxu Tian (Journal of Ocean University of China, 2021)

Disrupted pathways from frontal-parietal cortex to basal ganglia and cerebellum in patients with unmedicated obsessive compulsive disorder as observed by whole-brain resting-state effective connectivity analysis – a small sample pilot study - Wei Liu; Minghui Hua; Jun Qin; Qiuju Tang; Yunyi Han; Hongjun Tian; Daxiang Lian; Zhengqing Zhang; Wenqiang Wang; Chunxiang Wang; Ce Chen; Deguo Jiang; et al. (Brain Imaging and Behavior, 2021)

Can phosphorus (P)-releasing bacteria and earthworm (Eisenia fetida L.) co-enhance soil P mobilization and mycorrhizal P uptake by maize (Zea mays L.)? - Junbo Liu; Junli Hu; Zhang Cheng; Minghui Li; Zihao Liu; Junhua Wang; Xiangui Lin (Journal of Soils and Sediments, 2021)

The better suppression of pepper Phytophthora blight by arbuscular mycorrhizal (AM) fungus than Purpureocillium lilacinum alone or combined with AM fungus - Junli Hu; Shaowei Hou; Minghui Li; Junhua Wang; Fuyong Wu; Xiangui Lin (Journal of Soils and Sediments, 2020)

Concomitant biocontrol of pepper Phytophthora blight by soil indigenous arbuscular mycorrhizal fungi via upfront film-mulching with reductive fertilizer and tobacco waste - Shaowei Hou; Yu Zhang; Minghui Li; Homgmin Liu; Fuyong Wu; Junli Hu; Xiangui Lin (Journal of Soils and Sediments, 2020)

Intercropping with sweet corn (Zea mays L. var. rugosa Bonaf.) expands P acquisition channels of chili pepper (Capsicum annuum L.) via arbuscular mycorrhizal hyphal networks - Junli Hu; Minghui Li; Homgmin Liu; Qi Zhao; Xiangui Lin (Journal of Soils and Sediments, 2019)

Regulatory Roles of Peroxisomal Metabolic Pathways Involved in Musk Secretion in Muskrats - Meishan Zhang; Shuang Yang; Minghui Shi; Shumiao Zhang; Tianxiang Zhang; Yimeng Li; Shanghua Xu; Muha Cha; Yuping Meng; Shaobi Lin; Juan Yu; Xuxin Li; et al. (The Journal of Membrane Biology, 2019)

The fecal virome of red-crowned cranes - Yan Wang; Shixing Yang; Dawei Liu; Chenglin Zhou; Wang Li; Yuan Lin; Xiaochun Wang; Quan Shen; Hua Wang; Chuang Li; Minghui Zong; Yuzhu Ding; et al. (Archives of Virology, 2019)

TGF-β1 Restores Hippocampal Synaptic Plasticity and Memory in Alzheimer Model via the PI3K/Akt/Wnt/β-Catenin Signaling Pathway - Yueqiang Hu; Wei Chen; Lin Wu; Lingfei Jiang; Ni Liang; Lulu Tan; Minghui Liang; Nong Tang (Journal of Molecular Neuroscience, 2019)

Short-term effects of ambient air pollutants and myocardial infarction in Changzhou, China - Yongquan Yu; Shen Yao; Huibin Dong; Minghui Ji; Zhiyong Chen; Guiying Li; Xingjuan Yao; Shou-Lin Wang; Zhan Zhang (Environmental Science and Pollution Research, 2018)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

miR-138-1* regulates aflatoxin B1-induced malignant transformation of BEAS-2B cells by targeting PDK1 - Yun Wang; Zhan Zhang; Huanqiang Wang; Yudong Zhang; Minghui Ji; Hengsen Xu; Chao Wang; Zhenzhen Sun; Weimin Gao; Shou-Lin Wang (Archives of Toxicology, 2016)

Molecular Cloning and Characterization of Two Genes Encoding Tryptophan Decarboxylase from Aegilops variabilis with Resistance to the Cereal Cyst Nematode (Heterodera avenae) and Root-Knot Nematode (Meloidogyne naasi) - Lin Li; Minghui Zheng; Hai Long; Guangbing Deng; Atsushi Ishihara; Feng Liu; Junjun Liang; Zhifen Pan; Maoqun Yu (Plant Molecular Biology Reporter, 2016)

Continuous Treatment of Phenol over an Fe2O3/γ-Al2O3 Catalyst in a Fixed-Bed Reactor - Minghui Lu; Yue Yao; Lulu Gao; Dongmei Mo; Fang Lin; Shuxiang Lu (Water, Air, & Soil Pollution, 2015)

Residues and dissipation of trifloxystrobin and its metabolite in tomatoes and soil - Lin Wang; Wenming Li; Puyu Li; Minghui Li; Shuo Chen; Lijun Han (Environmental Monitoring and Assessment, 2014)

Spatial and temporal variability of colored dissolved organic matter absorption properties in the Taiwan Strait - Hui Lin; Weidong Guo; Minghui Hu; Cai Lin; Weidong Ji (Acta Oceanologica Sinica, 2012)